2021
DOI: 10.1136/medethics-2021-107291
|View full text |Cite
|
Sign up to set email alerts
|

Reflections of methodological and ethical challenges in conducting research during COVID-19 involving resettled refugee youth in Canada

Abstract: Research involving migrant youth involves navigating and negotiating complex challenges in order to uphold their rights and dignity, but also all while maintaining scientific rigour. COVID-19 has changed the global landscape within many domains and has increasingly highlighted inequities that exist. With restrictions focusing on maintaining physical distancing set in place to curb the spread of the virus, conducting in-person research becomes complicated. This article reflects on the ethical and methodological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 40 publications
(32 reference statements)
0
6
0
1
Order By: Relevance
“…The difficulty of delivering research with young people during the height of COVID-19 restrictions in the UK have been articulated elsewhere (e.g. Salam et al, 2022), and this study was certainly not immune to these challenges. Our primary limitation relates to the short time window at our disposal for gathering data.…”
Section: Limitationsmentioning
confidence: 83%
“…The difficulty of delivering research with young people during the height of COVID-19 restrictions in the UK have been articulated elsewhere (e.g. Salam et al, 2022), and this study was certainly not immune to these challenges. Our primary limitation relates to the short time window at our disposal for gathering data.…”
Section: Limitationsmentioning
confidence: 83%
“…There is a growing literature that critically considers online videoconferencing methods for consultation activities or research [ 38 , 39 , 40 , 41 , 42 ], with some considering specific platforms such as Skype [ 40 , 43 , 44 , 45 ] or Zoom [ 38 , 39 , 46 ]. Less literature exists on engaging children in videoconferencing, although platforms, such as Skype [ 45 ] and Zoom [ 47 ], are being used to generate qualitative interview and other creative data effectively and safely. Work conducted prior to the pandemic has demonstrated that participants find Zoom relatively easy to use, cost-effective and generally rated Zoom above alternative methods such as face-to-face, telephone or other video communication platforms [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is also essential for the interviewer to have a good knowledge of the asylum system in the country of study and of the implications of the migration process for the person being interviewed (Ogilvie et al , 2008). Researchers must recognize the power dynamic that can be induced between the young participant and the investigator (Dona et al , 2019), as it could have consequences, such as making a young person feel obliged to participate (Salam et al , 2021).…”
Section: Methodsmentioning
confidence: 99%